Pengaruh Model Pembelajaran PAIKEM Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti siswa kelas XI SMA N 1 Parlilitan Tahun Ajaran 2023/2024 - Ellida Lusiva Hasugian; Boho Parulian Pardede; Raikhapoor Raikhapoor; Meditatio Situmorang; Frainskoy Rio Naibaho (Simpati, 2024)
The research aims to find out how much influence the model hasPAIKEM learning towards learning motivation for Christian Religious Education andCharacteristics of class XI students of SMA Negeri 1 Parlilitan for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between PAIKEM learning model on motivation to learn Religious Education Christianity and Character, Class XI students of SMA Negeri 1 Parlilitan, Academic Year 2023/2024. Descriptive and inferential quantitative research methods. Whole population Class XI students of SMA Negeri 1 Parlilitan for the 2023/2024 academic year who are religious There are 150 Protestant Christians. Random samples (random sampling) namely 25% of the total population, namely 38 people. The research instrument is: closed questionnaire. The results of data analysis obtained: a) rcount = 0.554> rtable = 0.320 and tcount=3.993>ttable=2.02809 shows that there is a positive relationship and significant relationship between the PAIKEM learning model and learning motivation Christian Religious Education and Character Education for class XI students of SMA Negeri 1Parlilitan Academic Year 2023/2024. b) Regression equation Y  25.88 0.404X c) The determination test revealed that the magnitude of the effect was 30.69%. d) Hypothesis test is obtained Fcount=15.933>Ftable=3.23 then H0 is rejected and Ha is accepted. Research concludes that there is a positive and significant influence between the PAIKEM learning model and educational learning motivation Christian Religion and Character, Class XI students of SMA Negeri 1 Parlilitan Tahun Teachings 2023/2024.